2011
DOI: 10.1155/2011/195271
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Vitamin C Reduces Blood Glucose and Improves Glycosylated Hemoglobin in Type 2 Diabetes Mellitus: A Randomized, Double-Blind Study

Abstract: No study has ever examined the effect of vitamin C with metformin on fasting (FBS) and postmeal blood glucose (PMBG) as well as glycosylated hemoglobin (HbA1c) in the treatment of type 2 diabetes mellitus (DM). The goal was to examine the effect of oral vitamin C with metformin on FBS, PMBG, HbA1c, and plasma ascorbic acid level (PAA) with type 2 DM. Seventy patients with type 2 DM participated in a prospective, double-blind, placebo-controlled, 12-week study. The patients with type 2 DM were divided randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 16 publications
5
61
0
4
Order By: Relevance
“…28 High but physiologic concentrations of ascorbic acid can directly inhibit erythrocyte aldose reductase thus preventing intracellular accumulation of sorbitol, or its sequelae, thereby inhibiting the progression of chronic diabetic complications; this is the rationale for the use of oral vitamin C supplements in diabetes. 9 Vitamin C as a result of its structural similarity to glucose can compete with it to reduce haemoglobin glycosylation in patients with type 2-diabetes. The reduction of glycosylated haemoglobin can reflect the decrease of total glycosylation of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 High but physiologic concentrations of ascorbic acid can directly inhibit erythrocyte aldose reductase thus preventing intracellular accumulation of sorbitol, or its sequelae, thereby inhibiting the progression of chronic diabetic complications; this is the rationale for the use of oral vitamin C supplements in diabetes. 9 Vitamin C as a result of its structural similarity to glucose can compete with it to reduce haemoglobin glycosylation in patients with type 2-diabetes. The reduction of glycosylated haemoglobin can reflect the decrease of total glycosylation of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…9 interconnecting systems of antioxidant micronutrients (minerals) and enzymes are also present to accomplish the body's defence against oxidative stress. Vitamin C is structurally similar to glucose and can replace it in many chemical reactions, and thus is effective in prevention of non-enzymatic glycosylation of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that a chronic VC administration improved whole body glucose disposal and nonoxidative glucose metabolism (63). Besides, additional positive effects of VC on these carbohydrate metabolism markers have been demonstrated in patients following pharmacological treatments in comparison with those in the placebo group, suggesting a possible use of this vitamin in combination with drugs (86).…”
Section: D) Glucocorticoid Metabolismmentioning
confidence: 97%
“…Increasing evidence from both experimental and clinical studies suggests that oxidative stress plays a major role in the pathogenesis of type 2 diabetes: abnormally high levels of free radicals and the simultaneous decline of antioxidant defence mechanisms can lead to damage of cellular organelles and enzymes, increased lipid peroxidation and development of insulin resistance [3][4][5]. Moreover, previous studies have highlighted how increased intake of common dietary antioxidants such as vitamin E and vitamin C increase insulin sensitivity, reduce fasting and post-meal blood glucose and improve HbA 1c levels [6,7]. Other authors have reported a statistically significant decrease in total antioxidant status and increase in levels of oxidative stress markers in individuals with type 2 diabetes compared with healthy individuals, and have suggested that these levels could be considered markers of early disease and predictors of type 2 diabetes complications [8].…”
Section: Introductionmentioning
confidence: 99%